# L2 transformation reduces to the L1 transformation

Pyrokenesis
Hello.

I am having trouble answering the following question:

"Show that the L2 transformation reduces to the L1 transformation when the two reference frames are in standard configuration."

Am I wrong to assume that r = xi + yj + zk

Any help would be beautiful!

Thanx much

"Show that the L2 transformation reduces to the L1 transformation when the two reference frames are in standard configuration."

I assume that the source of this question defines what the L2 and L1 transformations are, as well as what two reference frames are being compared. Please elaborate.

Pyrokenesis
The L2 transformations are as follows:

r' = r + &gamma;v^[(1 - 1/&gamma;)(r.v^) - &beta;ct];

ct' = &gamma;(ct - r.&beta;);

where &beta; = v/c & v^ is the unit vector in the direction of v.

The L1 transformations are:

x' = &gamma;(x - &beta;ct);
y' = y;
z' = z;

ct' = &gamma;(ct - &beta;x);

where &beta; = v/c.

All are viewed in the S' frame.